ANTIOXIDANT AND ANTICANCER ACTIVITIES OF MURBEI (Morus alba L.) STEM EXTRACT ON IN VITRO WiDr CANCER CELLS - Asril Burhan; Akbar Awaluddin; Zulham Zulham; Burhanuddin Taebe; Abdul Gafur (Universitas Sanata Dharma, 2020)
Mulberry (Morus alba L.) is considered as an important plant in traditional Chinese medicine, due to its various compounds, including phenols and flavanoids, which have antioxidant properties so that it can be a potential anticancer candidate. This study aimed to determine the antioxidant activity, phenolic content, and potential anticancer activity in Mulberry stem extract. The extraction was done by maceration using ethanol as the solvent, while antioxidant activity test used ABTS (2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) method, phenolic content determination used Folin-Ciocalteu reagents, and anticancer activity test used the MTT (3-(4,5- dimetiltiazol-2-il)-2,5-difenil tetrazolium bromida) method on WiDr cancer cells and Vero cells. The result of total phenolic Mulberry stem extract was 35.9%, the antioxidant activity value was 83.18 µg/mL, the IC50 value for anticancer activity for WiDr cells was 71.24 µg/mL and Vero cells IC50 value was 154.241 µg/mL. It could be concluded that the Mulberry stem ethanol extract has strong antioxidant activity and has the potential to be an anticancer agent selectively against WiDr cancer cells.